Copyrolysis of peanut shells and cassava starch mixtures: Effect of the components proportion - Gurevich Messina, Luciano Ignacio (2015)
Copyrolysis of peanut (Arachis hypogaea) shells and cassava (Manihot esculenta) starch using mixtures of different proportions was examined to improve yield of the bio-oil and its quality. Pyrolysis of the individual components was also investigated in order to quantify the improvement of the measured properties. The kinetics of pyrolysis/copyrolysis was characterized by thermogravimetrical analysis and the application of two different models: one which takes into account the deactivation of the solid, and another one which assumes a normal distribution of the activation energy. Interactions between the starch and the shells were inferred since maximum reaction rates were, in all cases, lower than the weighed average values obtained for the pyrolysis of the individual components. Furthermore, both the bio-oil yield and the water content of the liquids showed synergistic effects. A mixture composed by 75 wt% of starch and 25 wt% of peanut shells led to maximize the yield of the bio-oil (58.2 wt%), while its water content was reduced in 3.4% in comparison with the value expected from the weighed average of the individual results. On the other hand, the addition of the starch to the peanut shells led to a bio-char with less ash content. It could be more suitable for further combustion in steam boilers.